2008
DOI: 10.1371/journal.pone.0003336
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Human Umbilical Mesenchymal Stem Cells from Wharton's Jelly after Complete Transection of the Rat Spinal Cord

Abstract: BackgroundHuman umbilical mesenchymal stem cells (HUMSCs) isolated from Wharton's jelly of the umbilical cord can be easily obtained and processed compared with embryonic or bone marrow stem cells. These cells may be a valuable source in the repair of spinal cord injury.Methodology/Principal FindingsWe examine the effects of HUMSC transplantation after complete spinal cord transection in rats. Approximately 5×105 HUMSCs were transplanted into the lesion site. Three groups of rats were implanted with either unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
153
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(165 citation statements)
references
References 67 publications
10
153
0
2
Order By: Relevance
“…HMSCs isolated from Wharton's jelly can be easily and ethically obtained and processed compared with embryonic or bone marrow stem cells. These stem cells may be a valuable source in the repair of the peripheral nervous system with capacity to differentiate into neuroglial-like cells ( Fu et al, 2006;Yang et al, 2008). The transplanted HMSCs were also able to promote local blood vessel formation and release the neuro-trophic factors brain-derived neurotrophic factor (BDNF) and glial cell line-derived neurotrophic factor (GDNF) ( Fu et al, 2006;Wang et al, 2004).…”
Section: Groupmentioning
confidence: 99%
“…HMSCs isolated from Wharton's jelly can be easily and ethically obtained and processed compared with embryonic or bone marrow stem cells. These stem cells may be a valuable source in the repair of the peripheral nervous system with capacity to differentiate into neuroglial-like cells ( Fu et al, 2006;Yang et al, 2008). The transplanted HMSCs were also able to promote local blood vessel formation and release the neuro-trophic factors brain-derived neurotrophic factor (BDNF) and glial cell line-derived neurotrophic factor (GDNF) ( Fu et al, 2006;Wang et al, 2004).…”
Section: Groupmentioning
confidence: 99%
“…Yang et al reported that the transplantation of 5 × 10 5 hUC-MSCs at the lesion site after complete transection of the rat spinal cord promoted significant recovery of locomotion, stimulated the regrowth of injured corticospinal fibers, and increased the number of neurofilament-positive axons around the lesion site (6). Of note, these neuroprotective effects were associated with immunomodulation (a decrease in the microglial and astrocytic responses) and with increased Review Dalous et al levels of human growth factors such as basic fibroblast growth factor and NT-3.…”
Section: Effect Of Huc-mscs In Adult Preclinical Models Of Neurologicmentioning
confidence: 99%
“…Several reports have demonstrated neuroprotection after experimental hUC-MSC xenotransplantation with or without immunosuppressive treatment, and there is no consensus as to the need for immunosuppression for optimal neuroprotection. Some studies have shown the survival of numerous transplanted cells for periods as long as 4 mo, even though no immunosuppression was used (6,59,97). Contrarily, in similar animal models, few transplanted cells could be identified a few weeks after transplantation in immunosuppressed animals (98).…”
Section: Potential Shortcomings Of the Use Of Huc-mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been postulated that this neuroprotection may occur as a result of growth factor production by transplanted cells, and this theory is supported by transfection studies with growth factors such as glial cell line derived neurotrophic factor that have been shown to improve functional recovery after stroke in a rodent model (12). The other options may be inhibition of the host immune response and inflammation (20,23), improvement of vascularization (5) and suppression of glial scar formation (23). Alternatively, functional recovery could be elicited by axon growth and neural plasticity-promoting approaches that result in restoration of damaged and formation of new neural circuits that could become involved in functional recovery (5, 8,16).…”
Section: Survival and Migration Of Rbm-mscsmentioning
confidence: 99%